Hydrogen production using advanced reactors by steam methane reforming: A review - Ganguli, Arijit; Bhatt, Viraj (Frontiers in Thermal Engineering, 2023)
The present review focuses on the current progress on harnessing the potential of hydrogen production by Methane Steam Reforming (MSR). First, based on the prominent literature in last few years, the overall research efforts of hydrogen production using different feed stocks like ethanol, ammonia, glycerol, methanol and methane is presented. The presented data is based on reactor type, reactor operating conditions, catalyst used and yield of hydrogen to provide a general overview. Then, the most widely used process [steam methane reforming (SMR)/methane steam reforming (MSR)] are discussed. Major advanced reactors, the membrane reactors, Sorption Enhanced methane steam reforming reactors and micro-reactors are evaluated. The evaluation has been done based on parameters like residence time, surface area, scale-up, coke formation, conversion, space velocity and yield of hydrogen. The kinetic models available in recently published literature for each of these reactors have been presented with the rate constants and other parameters. The mechanism of coke formation and the rate expressions for the same have also been presented. While membrane reactors and sorption enhanced reactors have lot of advantages in terms of process intensification scale-up to industrial scale is still a challenge due to factors like membrane stability and fouling (in membrane reactors), decrease in yield with increasing WHSV (in case of Sorption Enhanced Reactors). Micro-reactors pose a higher potential in terms of higher yield and very low residence time in seconds though the volumes might be substantially lower than present industrial scale conventional reactors.